2011
DOI: 10.1007/s10530-011-0141-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fragmentation on the survival and growth of the invasive, clonal plant Alternanthera philoxeroides

Abstract: The capacity of small clonal fragments to survive and grow is a major factor in the spread of clonal plants, especially aquatic species. This study of the introduced, invasive, amphibious, stoloniferous herb Alternanthera philoxeroides in China tested the effects of fragment size, of loss of the stolon apex, and of the original position of a fragment within a clone before fragmentation on the survival and growth of fragments in a greenhouse experiment. The stolon internodes of plants consisting of one stolon w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 38 publications
(39 reference statements)
1
62
1
Order By: Relevance
“…Severance can release more distal ramets from apical dominance by more proximal ramets in various species (Evans and Whitney 1992;Balestri and Lardicci 2013;Gao et al 2013). In A. philoxeroides, severance from proximal ramets can induce distal ramets to produce more offspring with no change in the total mass of clonal fragments (Dong et al 2012 recently found that interactive effects of severance and environment on growth in mass and on production of new ramets differed in the grass Phalaris arundinacea, and clonal reproduction and total accumulation of mass show different effects of nutrient availability in the aquatic clonal plant Eichhornia crassipes (You et al 2014). Measures of reproduction and spread may thus require different treatment than measures of mass in models of effects of clonal integration in homogeneous environments.…”
Section: Discussionmentioning
confidence: 99%
“…Severance can release more distal ramets from apical dominance by more proximal ramets in various species (Evans and Whitney 1992;Balestri and Lardicci 2013;Gao et al 2013). In A. philoxeroides, severance from proximal ramets can induce distal ramets to produce more offspring with no change in the total mass of clonal fragments (Dong et al 2012 recently found that interactive effects of severance and environment on growth in mass and on production of new ramets differed in the grass Phalaris arundinacea, and clonal reproduction and total accumulation of mass show different effects of nutrient availability in the aquatic clonal plant Eichhornia crassipes (You et al 2014). Measures of reproduction and spread may thus require different treatment than measures of mass in models of effects of clonal integration in homogeneous environments.…”
Section: Discussionmentioning
confidence: 99%
“…This species is one of the world's worst invasive weeds and is listed as one of the 16 worst alien invasive weeds in China (Julien et al, 1995;Ma and Wang, 2005). A. philoxeroides often suffers natural disturbances, such as herbivory, mowing and trampling, which may fragment its clones into pieces Dong et al, 2010Dong et al, , 2012. In China, A. philoxeroides has extremely low genetic diversity (Xu et al, 2003;Wang et al, 2005), and clonal integration may play an important role in determining its growth and spread (Wang et al, , 2009Xu et al, 2010).…”
Section: Plant Speciesmentioning
confidence: 99%
“…Therefore clonal traits likely play an important role in community assembly and invasion; indeed several studies have demonstrated a link between clonality and invasion success (Otfinowski and Kenkel, 2008;Okada et al, 2009;Roiloa et al, 2010;Li and Wang, 2011;Dong et al, 2012). Though the importance of clonal traits is well-established, data on clonal traits in invasive plants are not as widely available as more commonly-measured leaf and seed characteristics (van Kleunen et al, 2010; but see Klimešová and de Bello, 2009).…”
Section: Introductionmentioning
confidence: 99%